Intubation-Related Dysphonia Following Extreme Preterm Birth: Case Studies in Behavioural Voice Intervention - Reynolds, Mary; Meldrum, S.; Simmer, K.; Vijayasekaran, S.; French, N. (2014)
Abstract Many more children than ever before survive and thrive following preterm birth (Saigal & Doyle, 2008). To date, research has focussed on medical, developmental, neurological, and behavioral outcomes. As the number of surviving children increases and survivors reach school age and beyond, it has become apparent that many children experience difficulties with voice production (French et al., 2013). Following preterm birth, endotracheal intubation may be necessary to deliver surfactant or relieve respiratory distress during the neonatal period (Ho, Subramaniam, Henderson-Smart, & Davis, 2002). Intubation injury to the larynx and resultant dysphonia are well described in the literature (Bray, Cavalli, Eze, Mills, & Hartley, 2010). This article presents a brief review of the literature relevant to intubation-related injury following preterm birth and 2 case studies of voice outcomes following a trial of behavioral voice therapy in extremely preterm children who were intubated.